2001
DOI: 10.1007/s102380100000
|View full text |Cite
|
Sign up to set email alerts
|

Primary biliary cirrhosis: lessons learned from an organic-specific disease

Abstract: Primary biliary cirrhosis is an autoimmune liver disease that predominantly affects women and is characterized by chronic progressive destruction of small intrahepatic bile ducts with portal inflammation and subsequent fibrosis. The serological hallmark is the presence of antimitochondrial antibodies, which are found in 95% of patients. These antibodies are directed against the 2-oxo-acid dehydrogenase complexes located on the inner membrane of mitochondria. Although the role of antimitochondrial antibodies in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…PBC is a female dominant autoimmune liver disease, characterized by the destruction of intrahepatic bile ducts and the production of high-titer anti-mitochondrial Abs (AMA). The major mitochondrial autoantigens recognized by AMA are the E2 components of the 2-oxo-dehydrogenase pathway, particularly pyruvate dehydrogenase complexes (PDC-E2) (4). One of the hallmarks of these autoantigens is that they are each lipoylated in a region localized to the immunodominant peptide recognized by both humoral and cellular autoimmune responses by PBC patients (5)(6)(7)(8).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…PBC is a female dominant autoimmune liver disease, characterized by the destruction of intrahepatic bile ducts and the production of high-titer anti-mitochondrial Abs (AMA). The major mitochondrial autoantigens recognized by AMA are the E2 components of the 2-oxo-dehydrogenase pathway, particularly pyruvate dehydrogenase complexes (PDC-E2) (4). One of the hallmarks of these autoantigens is that they are each lipoylated in a region localized to the immunodominant peptide recognized by both humoral and cellular autoimmune responses by PBC patients (5)(6)(7)(8).…”
mentioning
confidence: 99%
“…Recently, we have shown that organic molecules known as xenobiotic agents can be used to induce an autoimmune response that mimics the one found in primary biliary cirrhosis (PBC) 4 (3). PBC is a female dominant autoimmune liver disease, characterized by the destruction of intrahepatic bile ducts and the production of high-titer anti-mitochondrial Abs (AMA).…”
mentioning
confidence: 99%
“…It is accepted that liver fibrosis is reversible, whereas cirrhosis is generally irreversible. 26,31 The regenerative ability of the liver is excellent. The process is influenced by several growth factors and cytokines.…”
Section: Overview Of Liver Alterationsmentioning
confidence: 99%